Analisis Aspek Kepatuhan Wajib Pajak Bumi Dan Bangunan Perdesaan Dan Perkotaan (Pbb-P2) Di Bapenda Kabupaten Garut Tahun 2021 - Husudur, Misbah; Agustianto, Jiwa Pribadi; Yanuar, Ryan Dwi (Jurnal Ilmu Administrasi Publik, 2024)
The purpose of this study was to analyze the compliance aspects of rural and urban land and building (PBB-P2) taxpayers at the Bapenda (Regional Revenue Agency) of Garut Regency in 2021, the obstacles faced in increasing the compliance of PBB-P2 taxpayers at the Garut Regency Bapenda, and how to overcome these obstacles. This study used a qualitative methodology. The author used primary and secondary data obtained from interviews, literature study, and observation. A descriptive method was used, along with data analysis technique of interaction model. Based on the results of the study, it can be concluded that the compliance level of rural and urban land and building taxpayers in Garut Regency in 2021 was less than optimal as the compliance rate was 94.2%. The obstacles faced in increasing taxpayer compliance in Garut Regency Bapenda were related to the rules and sanctions for the imposition of PBB-P2. Efforts that can be made to overcome these obstacles are for the tax office to conduct direct campaigns to taxpayers; boththrough print media and social media.